Sinema Audio Berbasis Ambisonik: Menjelajahi Pengalaman Imersif untuk Penyandang Disabilitas Netra - Ibrahim Adi Surya; I Wayan Swandi; Desak Suarti Laksmi; I Gusti Putu Sudarta (Kartala Virtual Studies, 2026)
This study aims to explore the potential of ambisonic technology as an inclusive sound cinema medium for people with visual impairments. The background of this study stems from the limitations of conventional audio description, which is often considered to disrupt dramatic continuity, thus requiring an alternative based on immersive experiences. The research uses a practice-based qualitative approach with two main outputs, namely an ambisonic sound cinema prototype and empirical findings on the listening experience of visually impaired audiences. The research population consisted of students at SLBN A Pajajaran, Bandung City, with a purposive sample covering the categories of low vision, totally blind since birth, and light perception. The research process consisted of the creation of ambisonic sound cinema through sound dramaturgy, followed by listening tests using stereo headphones, and in-depth interviews to explore the respondents' perceptions. Data analysis was conducted qualitatively through reduction, categorization, and thematic interpretation. The results showed that respondents were able to clearly perceive the direction, space, and depth of sound, as well as understand the narrative flow without additional visuals or verbal narration. Ambisonic was considered more natural than audio description, although limitations in equipment, environmental noise, and technological literacy remained challenges. This study concludes that ambisonic has significant potential as an alternative form of accessibility to performing arts and entertainment for the visually impaired, while also contributing to the development of sound dramaturgy theory. Practical implications include integration into inclusive education, application in film production, and distribution through digital platforms. Thus, this study serves as a starting point for developing ambisonic sound cinema as a more equitable form of artistic and social innovation. Keywords: Ambisonic, sound cinema, visual impairment, inclusivity, sound dramaturgy, immersive experience